2009
DOI: 10.2478/s11534-009-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic and elastic properties of Ti2TlC, Zr2TlC and Hf2TlC

Abstract: Abstract:Using First-principle calculations, we have studied the structural, electronic and elastic properties of M 2 TlC, with M = Ti, Zr and Hf. Geometrical optimization of the unit cell is in good agreement with the available experimental data. The effect of high pressures, up to 20 GPa, on the lattice constants shows that the contractions are higher along the -axis than along the axis. We have observed a quadratic dependence of the lattice parameters versus the applied pressure. The band structures show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Withthe characteristics of metallic as well as ceramics materials 15 , where each group member contains at least two forms of ionic, covalent, or metallic chemical bonds 16 . The MAX phases such as Ti 3 SiC 2 and Ti 3 AlC 2 are a 312 class of layered ternaries where the individual phases differ by the number of M-layers parting the A-layers in the 312-MAX phases 17 21 . These compounds combine some characteristics of metals like strong compressive strength, high fracturing strength, hardness, ductility, good electrical and thermal conductivity, high stiffness, damage tolerance, relatively low thermal expansion coefficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Withthe characteristics of metallic as well as ceramics materials 15 , where each group member contains at least two forms of ionic, covalent, or metallic chemical bonds 16 . The MAX phases such as Ti 3 SiC 2 and Ti 3 AlC 2 are a 312 class of layered ternaries where the individual phases differ by the number of M-layers parting the A-layers in the 312-MAX phases 17 21 . These compounds combine some characteristics of metals like strong compressive strength, high fracturing strength, hardness, ductility, good electrical and thermal conductivity, high stiffness, damage tolerance, relatively low thermal expansion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…First-principles approaches are widely employed to study the properties of MAX phases, for example, M 2 GaN (M = Ti, V and Cr) 27 , Ti 2 TlC, Zr 2 TlC, and Hf 2 TlC 17 , 23 , Ti 3 AlC 2 and Ti 2 SiC 2 20 . Zhou et al 28 reported the distribution of charge density on the (1120) plane of Ti 3 AlC 2 , where robust directional Ti-C-Ti-C-Ti covalent bond chains were observed that linked to fairly weaker Ti–Al covalent bindings.…”
Section: Introductionmentioning
confidence: 99%
“…Specific forms of MAX phases called 211, 312, or 413 (and higher orders such as 514, 615, and 716) are known in the literature. These numbers denote the stoichiometry of MAX phase materials, for example, Ti2SiC and Ti2AlC represent 211 MAX phases, Ti3SiC2 and Ti3AlC2 denote 312-MAX phase while 413-type are the Ti4SiC3 and Ti4AlC3, indicating that the individual phases differ by the number of M layers parting the A-layers, that is there are two in the 211-type, three in the 312-type, and four M-layers in the 413 MAX phase-type [1][2][3]8 .…”
Section: Introductionmentioning
confidence: 99%
“…MAX phases are useful in numerous applications due to their unique, hybrid ceramic/metal properties, that result from their structure as well as their atomic arrangements 1,8,9 . More categorically, these materials are considered for purposes in extreme environments as they exhibit outstanding oxidation resistance and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation